The Encyclopedia of wood : a tree- by- tree guide to the world's most versatile resource - Walker, Adian; Makepeace, John (Facts on File, 1989)
"The Encyclopedia of Wood is the most informative and comprehensive guide for all those who fully appreciate the beauty of wood. It is much more than a craftperson's guide. The anatomy and life cycle of trees are described, as are the subtleties of grain, pattern, figure, and color. Forest types from around the world are explained and illustrated, with a special section on the complex subject of deforestation and conservation. The processes that wood undergoes between the forest and the end user are explored, including how timber is cut and the way in which this affects its uses. Stress and grading, drying and conversion, and advanced wood manufacturing technology are all covered in detail." "The book's core is an A-Z directory of 150 of the world's most popular and beautiful timbers. Growth and distribution, appearance, mechanical and working properties, and applications are listed, with each wood superbly illustrated in color.". "The Encyclopedia of Wood is unique in its appeal to designers, engineers, artists, craftspeople, and enthusiasts alike. Generously illustrated, informative, and thoroughly readable, it is the essential companion for users and lovers of the earth's best-loved natural resource."--BOOK JACKET.